THE VIOLENCE OF ABSTRACTION: Fredric Jameson, the "Asiatic Mode," and the Problem of Asia. - Torres Reyes, Maria Luisa; Lee, Alex Taek-Gwang (Kritika Kultura, 2026)
This forum introduction revisits Fredric Jameson’s engagement with Asia by focusing on a central tension in his work: the productive power of his world-historical method and the limitations of its reliance on the typological figure of the "Asiatic mode of production." Rather than treating this tension as grounds for either dismissal or recuperation, the essay argues that Jameson’s categories become most useful precisely at the point where they encounter their limits, opening the possibility for alternative modes of theoretical practice. It proposes refunctioning and provincializing as complementary methodologies through which inherited concepts are displaced, reworked, and renewed in relation to the heterogeneous histories of Asia, understood not as a singular civilizational object but as a field of uneven, conflictual, and overlapping historical trajectories. Reading across contributions from China, Korea, Turkey, Indonesia, and the Philippines, the forum demonstrates how concepts such as national allegory, postmodernism, and cognitive mapping acquire new analytical force when engaged with semiperipheral, postcolonial, and archipelagic conditions. These essays show that theory does not simply travel across contexts; it is transformed through them, revealing Jameson’s legacy less as a closed body of thought than as an ongoing and unfinished field of critical production.